Gray Whale (Eschrictius robustus) Call Types Recorded During Migration off the West Coast of Vancouver Island - Burnham, Rianna; Duffus, David; Mouy, Xavier (Frontiers in Marine Science, 2018)
Gray whale (Eschrichtius robustus) vocalizing behaviour varies over its range, both in call type and frequency. This study adds to the growing body of passive acoustic research outside of the calving/breeding lagoons, and moves toward a description of calling behaviours throughout the whales’ range. Data are presented here from acoustic surveys for two northward and one southward migration. We found gray whales to be highly sonorous, with extensive calling during the study periods of February to May for northward migrations and September to the end of January for southward travel. Low frequency moans were the most prevalent call type, with others, including knocks, up- and down sweeps, and rumbles, recorded in varying numbers. We hypothesize that calling is an aid for navigation and orientation of the herd along the migration route, in addition to holding more social functions usually assigned to baleen whale calling.